Evaluating pharmacist input into the pharmaceutical care of patients in dispensing medical practices in remote and rural areas of Scotland. (8th March 2017) - Stewart, Derek; Anthony, Breda; Morrison, Clare; MacRae, Yvonne; Dixon, Lucy; Friel, Emer; Yoong, Evelyn; Cunningham, Scott; MacLure, Katie
Abstract: Background: The Highlands and the Western Isles are the two most remote and rural areas of Scotland, with many medical practices in areas where pharmacies would not be viable. Recent regulations state that that dispensing medical practices in these areas must receive pharmacist support for patients who would benefit. Objective: This study aimed to evaluate pilot services, which centred on the provision of patient centred pharmaceutical care. Methods: A realist type evaluation was conducted by an independent research team comprising collecting quantitative data around what occurred during the consultation followed by interviews with purposive samples of staff ( n = 14) and patients ( n = 18). Results: A total of 873 medicines related issues were identified in 473 patients reviewed, with the main issue being 'inappropriate dose, frequency, duration'. Just under half (39.7%) of issues were managed by the pharmacist without any medical input. Interviews indicated a high level of appreciation, although there was an increase in workload for some staff. While the need for telephone based pharmacist consultations for some patients was understood, there was a preference for face to face. All were supportive of continuing and extending the service. Conclusion: The clinical pharmacist service was both needed and valued highly by staff and patients. In Scotland, this aligns with the Government vision and action plan, 'Prescription for Excellence', that by 2023 all patient facing pharmacists will be independent prescribers with those in remote and rural areas entitled to 'equity of access to such expertise'.